1993
DOI: 10.1136/jmg.30.6.518
|View full text |Cite
|
Sign up to set email alerts
|

Deletion 9p and sex reversal.

Abstract: We report a case of a female infant with a de novo deletion of the short arm of chromosome 9, sex reversal, and an apparently intact SRY gene. Sex reversal has been reported in a number of subjects with a normal Y chromosome and a deletion of the terminal segment of the short arm of chromosome 9. The factors controlling early development of the male testes are unknown. There are likely to be many genes involved and we present additional evidence that one of these is situated on the end of the short arm of chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
76
0
3

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(80 citation statements)
references
References 21 publications
1
76
0
3
Order By: Relevance
“…DM domain genes have been implicated in vertebrate sexual development by chromosomal location and by embryonic expression. Human DMRT1 maps to an autosomal locus (9p24.3) that, when hemizygous, is associated with defective testicular development and consequent 46,XY feminization (Crocker et al 1988;Hoo et al 1989;Bennett et al 1993;Veitia et al 1997Veitia et al , 1998Flejter et al 1998;Guioli et al 1998;Raymond et al 1998). In birds, which have ZZ/ZW sex determination, Dmrt1 is found on the Z chromosome (Nanda et al 1999), again suggesting that two doses of Dmrt1 (ZZ=male) might be necessary for testis development.…”
mentioning
confidence: 99%
“…DM domain genes have been implicated in vertebrate sexual development by chromosomal location and by embryonic expression. Human DMRT1 maps to an autosomal locus (9p24.3) that, when hemizygous, is associated with defective testicular development and consequent 46,XY feminization (Crocker et al 1988;Hoo et al 1989;Bennett et al 1993;Veitia et al 1997Veitia et al , 1998Flejter et al 1998;Guioli et al 1998;Raymond et al 1998). In birds, which have ZZ/ZW sex determination, Dmrt1 is found on the Z chromosome (Nanda et al 1999), again suggesting that two doses of Dmrt1 (ZZ=male) might be necessary for testis development.…”
mentioning
confidence: 99%
“…In addition, our patient showed symptoms of AMC, which have not previously been reported in patients with de novo 9p deletion syndrome. Various studies have reported that 9p deletion syndrome is caused by a partial monosomy of 9p, with breakpoint sites mainly in the regions 9p22 to 9p24 5) .…”
Section: Discussionmentioning
confidence: 99%
“…DMRT1 activates testis specific genes such as Sox9 and Sox8, and represses ovary specific genes encoding Fox12, Wnt4 and R spondin 1 signaling proteins, and estrogen receptors 2,5,7) . CER1…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Em 70% dos pacientes 46,XY, estão presentes órgãos genitais anormais e seis casos extremos de reversão sexual foram publicados (38). Rossodivita e col. relatam dois casos de alterações no cromossomo 9 com hipogonadismo secundário e grave insuficiência testicular (39). A disfunção testicular nestes casos poderia estar relacionada às fases iniciais da determinação sexual, cujos fatores controladores ainda não são bem conhecidos.…”
Section: Outros Genes Candidatos a Integrarem A Cascata De Determinaçunclassified